Are Diamonds Forever? : Using the Permanent Income Hypothesis to Analyze Botswana's Reliance on Diamond Revenue - Basdevant, Olivier (IMF Working Papers; Working Paper ;, 2008)
This study assesses the sustainability of Botswana's diamond-related fiscal revenue. Diamond reserves are not adequate to generate enough permanent revenue to sustain a high level of expenditure. Under the current fiscal rule that no debt may be accumulated, Botswana will have to save more to avoid an abrupt adjustment in the medium term.